Genome sequence of nitratireductor aquibiodomus strain RA22 - Singh, Ajit; Jangir, Pramod Kumar; Kumari, Chanchal; Sharma, Rakesh (Journal of Bacteriology, 2012)
The genus Nitratireductor represents nitrate-reducing bacteria from the family Phyllobacteriaceae. Here we report the draft genome sequence of Nitratireductor aquibiodomus strain RA22, which contains 4,592,790 bp, with a G+C content of 61.30%, and has 4,241 protein coding genes.

Genome sequence of the alkaliphilic bacterium nitritalea halalkaliphila type strain LW7, isolated from Lonar Lake, India - Jangir, Pramod Kumar; Singh, Ajit; Shivaji, S.; Sharma, Rakesh (Journal of Bacteriology, 2012)
An alkaliphilic bacterium, Nitritalea halalkaliphila LW7, which belongs to the family Cyclobacteriacae in the phylum Bacteroidetes, was isolated from Lonar Lake in Maharastra, India. Here we announce the draft genome sequence of the type strain LW7, which contains 3,633,701 bp with a G+C content of 48.58%.